Simulators of Squamous Cell Carcinoma of the Skin: Diagnostic Challenges on Small Biopsies and Clinicopathological Correlation - Kong-Bing Tan; Sze-Hwa Tan; Derrick Chen-Wee Aw; Huma Jaffar; Thiam-Chye Lim; Shu-Jin Lee; Yoke-Sun Lee (Journal of Skin Cancer)
Squamous cell carcinoma (SCC) is a common and important primary cutaneous malignancy. On skin biopsies, SCC is characterized by significant squamous cell atypia, abnormal keratinization, and invasive features. Diagnostic challenges may occasionally arise, especially in the setting of small punch biopsies or superficial shave biopsies, where only part of the lesion may be assessable by the pathologist. Benign mimics of SCC include pseudoepitheliomatous hyperplasia, eccrine squamous syringometaplasia, inverted follicular keratosis, and keratoacanthoma, while malignant mimics of SCC include basal cell carcinoma, melanoma, and metastatic carcinoma. The careful application of time-honored diagnostic criteria, close clinicopathological correlation and a selective request for a further, deeper, or wider biopsy remain the most useful strategies to clinch the correct diagnosis. This review aims to present the key differential diagnoses of SCC, to discuss common diagnostic pitfalls, and to recommend ways to deal with diagnostically challenging cases.